PERANAN ADMINISTRASI KEPEGAWAIAN DALAM MENINGKATKAN KINERJA PEGAWAI PADA KANTOR CAMAT KECAMATAN PLAJU KOTA PALEMBANG - Mayamin Mayamin (Jurnal Ilmiah Administrasi Dan Sosial, 2022)
The nature of the functions or activities of the State's administrative staff is very broad and includes the development of an organizational structure for implementing staffing programs, systematic clarification of positions and fair salary planning, good recruitment, selection of employees to guarantee placement in suitable positions, planning for promotions broad, assessment of pastoral skills, planning for promotions primarily based on employee skills, activities to improve human relations, and activities to maintain and maintain employee morale and discipline of employeesThe purpose of this study, is to determine the implementation of personnel administration in improving employee performance in the district of Palembang City Plaju and To find out the inhibiting factors in the implementation of personnel administration in improving employee performance in the district of Palembang City PlajuThe results of the study, which were strengthened by interview data, found that the Role of Personnel Administration at the sub-district office of Plaju sub-district of Palembang had been going well but needed to be further improved so that it was truly in accordance with the Standard Operating Procedure (SOP). The factors inhibiting the implementation of the administration of employees in the sub-district office of Plaju, Palembang, namely not yet optimal facilities and infrastructure such as internet bandwidth bandwidth is still weak, so employees in carrying out their work are often disrupted by frequent sudden policies given by the leadership. those who want to make a family card often carry incomplete requirements so that the making of the family card is obstructed and the files accumulate.  Keywords: Administrative staff and Performance